The Influence of Lifestyle, Product Quality and Price on Beef Purchasing Decisions at the Lubuk Basung – Geragahan Union Market - Kurniawan, Agung; Yulasmi, Yulasmi; Putra, Ramdani Bayu (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study was to determine the effect of lifestyle, product quality and price on beef purchasing decisions at the Lubuk Basung Geragahan Union Market. The population in this study were all consumers in the Lubuk Basung Geragahan market. The determination of the sample was carried out randomly using the Slovin formula and obtained a sample of 100 respondents. Methods of data collection through surveys and distribution of questionnaires to consumers as respondents for 1 week. The data analysis technique used was Structural Equation Modeling (SEM) Analysis with Partial Least Square (PLS). The results showed that lifestyle, product quality and price on purchasing decisions were in the fairly good category. Then hypothesis testing showed that variable Style There is a positive and significant influence on the beef buyer's decision at the Lubuk Basung-Gerahan Union Market, Product Quality There is a positive and significant influence on the Beef Buyer's Decision at the Lubuk Basung-Gerahan Union Market, Price There is a positive and significant influence on beef buyer decisions at the Lubuk Basung-Geragah Unio Market.